Integrated Pest Management for Stored Grain: Potential Natural Biological Control by a Parasitoid Wasp Community - Avichai Harush (MDPI AG, 2021)
Insect contamination of stored grain is a major concern for the grain industry. Phosphine is currently the standard fumigant used to control insect pests in stored grain. However, some species and populations of insects that infest stored grain exhibit resistance to this fumigant and consumers are concerned about pesticide residues. Therefore, alternative methods of effective pest control are needed to partially or completely replace the use of phosphine. There is growing interest in biological control via parasitoid wasps. However, there is evidence that biological control will succeed only if used alongside other pest-management measures. Integrating biological control with the use of chemical insecticide is challenging and may lead to severe reductions in parasitoid survival and success. The main aim of the current study is to shed light on a greatly overlooked issue: the parasitoid community found in stored grain before and after phosphine treatment. The current study results indicate that there is a high level of parasitoid biodiversity within grain stores. We found common parasitoids at both semi-arid and Mediterranean sites, suggesting that those parasitoids can be active across a wide range of abiotic conditions. This research indicates that the community may recover even though phosphine has an immediate negative effect on a parasitoid community. Nevertheless, the parasitoid wasps seem to reduce the host population insufficiently. In light of the findings presented here, those interested in implementing pest-management strategies that include both phosphine treatment and biological control should consider conservation and augmentation of the naturally occurring parasitoid population. These studies should take into account interactions between and within parasitoid populations and phosphine distribution within the grain storage. To limit the effect of phosphine on the parasitoids, pest-management strategies should also reflect careful consideration of the timing of phosphine treatment and the need for sufficient refuge for the parasitoids.